Through the Looking Glass of Anthropology: the Nature, the Culture, the Semiotic - Sedda, Franciscu (Estudos Semióticos, 2021)
The essay analyzes a series of anthropological positions – in particular the ones of Lévi-Strauss, Geertz, Clifford, Appadurai, Latour, Viveiros de Castro, Descola – that cope with the relationship between nature and culture. It highlights the wealth of visions and strategies of these positions as well as their complex and often unnoticed correlations. The essay will show how the doublings of nature and culture, as well as the attempts to find loopholes to the opposition, take on significance in relation to semiotics and can inspire new models to think culture. In particular, anthropological work will give us the opportunity to identify in the semiotic that relational dimension that lies at the bottom of both nature and culture, which crosses the human and the non-human and challenges us as semioticians to rethink the value and form of our own relationalism.